Economic globalisation today : resource book - Sampat, Preeti (Bangalore : Books for Change, 2003)
On the role of transnational corporations in globalizing developing countries and policy implications.
Includes bibliographical references (p. 349-378).
Keywords: International business enterprises -- Developing countries; Globalization -- Economic aspects -- Developing countries